PAI Students' Perception of Problem-Based Learning at K.H. Abdurrahaman Wahid State Islamic University - Rizal, Zacky Al-Ghofir El-Muhtadi; Syahir, Ahmad (Proceeding International Conference on Education, 2025)
The application of Problem-Based Learning (PBL) in Islamic Religious Education (IRE) at the university level is an innovative strategy to address the challenges of relevance and student engagement in contextual learning. This study aims to: (1) understand the basic concepts of PBL; (2) explore students' perceptions of PBL implementation; and (3) identify the positive aspects of PBL as well as the challenges faced at UIN K.H. A. Wahid Pekalongan. The study employs a qualitative approach using in-depth interviews with PAI students participating in PBL-based learning. Data are analyzed thematically to uncover experiences, attitudes, and factors influencing the acceptance of the method. Results indicate that students view PBL positively as it promotes active engagement, critical thinking, collaboration, and communication skills. PBL is considered effective in connecting religious theory with current social issues. However, challenges such as discussion dominance by a few members, lack of self-confidence, differences in students' initial readiness, as well as time constraints and limited faculty guidance were also identified. This research highlights the need for a more inclusive PBL design, competent faculty facilitation, and fair group management strategies. The conclusion indicates that PBL is effective in improving the quality of PAI learning, but its success is highly dependent on the implementation context and the readiness of all stakeholders. These findings provide strategic recommendations for the development of innovative, relevant, and sustainable learning in religious education in the contemporary era.